Topological Indices of the Pent-Heptagonal Nanosheets VC5C7 and HC5C7 - Fei Deng; Xiujun Zhang; Mehdi Alaeiyan; Abid Mehboob; Mohammad Reza Farahani (Advances in Materials Science and Engineering)
In this paper, we computed the topological indices of pent-heptagonal nanosheet. Formulas for atom-bond connectivity index, fourth atom-bond connectivity index, Randić connectivity index, sum-connectivity index, first Zagreb index, second Zagreb index, augmented Zagreb index, modified Zagreb index, hyper Zagreb index, geometric-arithmetic index, fifth geometric-arithmetic index, Sanskruti index, forgotten index, and harmonic index of pent-heptagonal nanosheet have been derived.